2015
DOI: 10.1111/are.12772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioflocs on dietary protein requirement in juvenile whiteleg Shrimp,Litopenaeus vannamei

Abstract: A feeding trial was carried out to determine the effects of bioflocs on dietary protein requirement in juvenile whiteleg shrimp, Litopenaeus vannamei. Four bioflocs treatments (BFT) and one control group were managed: BFT fed diets 25% of crude protein (CP) (BFT‐25%), 30% CP (BFT‐30%), 35% CP (BFT‐35%) and 40% CP (BFT‐40%), and clear water control without bioflocs fed with 40% CP (CW‐40%). Triplicate groups of shrimp (initial body weight, 1.3 g) were fed one of the test diets at a ratio of 7% body weight daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 52 publications
8
37
0
Order By: Relevance
“…These results indicate that, under the conditions of this study, increasing the dietary protein content from 35 to 40% did not significantly ( P > 0.05) improve shrimp performance in terms of growth, survival, FCR, and PER. This concurs with Yun et al () who reported significant increase in growth of L . vannamei in biofloc systems as the dietary protein level increased from 25 to 30 to 35%, but no growth difference between 35 and 40% protein diets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate that, under the conditions of this study, increasing the dietary protein content from 35 to 40% did not significantly ( P > 0.05) improve shrimp performance in terms of growth, survival, FCR, and PER. This concurs with Yun et al () who reported significant increase in growth of L . vannamei in biofloc systems as the dietary protein level increased from 25 to 30 to 35%, but no growth difference between 35 and 40% protein diets.…”
Section: Discussionsupporting
confidence: 93%
“…However, the higher NO 3 ‐N, significantly lower ( P < 0.05) alkalinity, and higher bicarbonate requirement in EXP were the consequence of the higher nitrification activities in that treatment to nitrify the available ammonia (Loyless and Malone ; Ebeling et al ). This positive relationship between dietary protein content and nitrate accumulation has also been reported by Gómez‐Jimenez et al (), Correia et al (), and Yun et al (). The higher PO 4 concentration in EXP was likely due to the higher phosphorus content in the EXP feed (1.45 vs. 1.01%).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Brito et al (2016) recorded increased crude protein levels in shrimp (in whole bodies) reared in integrated biofloc systems. However, Jatobá et al (2014) and Yun et al (2016) did not find significantly different (p > 0.05) results for protein in whole bodies and muscle tissue in juvenile shrimp reared in a biofloc monoculture system and fed diets containing varying levels of protein.…”
Section: Variables Treatmentsmentioning
confidence: 64%
“…Correia et al (2014) and Yun et al (2016Yun et al ( ) demonstrated (1999 for white shrimp culture. This variable influences oxygen consumption, molt cycle, growth, survival, feed consumption rates, metabolic rate and ammonia excretion of shrimp, but did not limit the L. vannamei growth, because the performance variables were considered satisfactory for these conditions.…”
Section: Discussionmentioning
confidence: 98%